Low testosterone levels are predictive for incident atrial fibrillation and ischaemic stroke in men, but protective in women – results from the FINRISK study. (July 2018) - Zeller, Tanja; Schnabel, Renate B; Appelbaum, Sebastian; Ojeda, Francisco; Berisha, Filip; Schulte-Steinberg, Benedict; Brueckmann, Burkhard-Ekkehart; Kuulasmaa, Kari; Jousilahti, Pekka; Blankenberg, Stefan; Palosaari, Tarja; Salomaa, Veikko; et al.
Background: Atrial fibrillation is the most common serious abnormal heart rhythm, and a frequent cause of ischaemic stroke. Recent experimental studies, mainly in orchiectomised rats, report a relationship between sex hormones and atrial electrophysiology and electroanatomy. We aimed to evaluate whether low testosterone levels are predictive for atrial fibrillation and/or ischaemic stroke in men and women. Design and methods: The serum total testosterone levels were measured at baseline in a population cohort of 7892 subjects (3876 male, 4016 female), aged 25–74 years, using a commercially available immunoassay. The main outcome measure was atrial fibrillation or ischaemic stroke, whichever came first. Results: During a median follow-up of 13.8 years, a total of 629 subjects (8.0%) suffered from incident atrial fibrillation ( n = 426) and/or ischemic stroke ( n = 276). Cox regression analyses, adjusted for age (used as time-scale), geographical region, total cholesterol (log), high-density lipoprotein-cholesterol (log), hypertension medication, known diabetes, smoking status, waist-hip-ratio, and time of blood drawn, documented differential predictive value of low sex-specific testosterone levels for atrial fibrillation and/or ischaemic stroke, in men and in women: Increasing levels were associated with lower risk in men (hazard ratio per one nmol/l increase 0.98 (95% confidence interval 0.93–1.00); p = 0.049). On the other hand, increasing testosterone levels were associated with higher risk in women (hazard ratio per one nmol/l increase 1.17 (95% confidence interval 1.02–1.36); p = 0.031). Conclusion: Our study indicates that low testosterone levels are associated with increased risk of future atrial fibrillation and/or ischaemic stroke in men, while they are protective in women.